Pernik-Pernik Metode dan Pendekatan dalam Penelitian Filologi (LP2M IAI NURUL HAKIM, 2021)
This article intends to examine the method and approach in philological research. It should be noted that philology is a difficult study, it is due to the return of the text to a form that is closer to the his original. Even though the text has existed for hundreds or even thousands of years ago, so that the text is prone to corruption, lakuna, interpolation, omission, ditography, haplography, transposition and others. Therefore it is necessary to held the research related to method and approach in philological research. This type of research is classified as qualitative research. The method used is descriptive analysis method. The findings obtained that is: (1) In general, the method of philological studies is divided into two types: a) The method of research on manuscript, b) The method of text criticism. The stages of the method of research on manuscript include: manuscript inventory, manuscript description, manuscript classification, manuscript comparison, manuscript lineage or stema and determination of the basic manuscript. As for related the method of text criticism there are two kinds: uniqus coder and multus coder. If there is only one manuscript, it is pursued in two ways: the diplomatic edition and the standard edition covered by the uniqus coder frame. Meanwhile, if the manuscript is more than one, then there are four methods, that is the intuitive, objective, combined and basic method which are covered in the multus coder frame. The next step is stema drafting and text reconstruction; (2) The approach in philological research according Ronald Tanaka includes a macro approach and a micro approach. Even though researchers use a macro approach, researchers still can’t ignore the micro approach, because both are complementary. With the combination of the two approaches, it is hoped that the maximum level of philological results can be obtained. Another approach that can be used is the linguistic discourse approach and the historical criticism approach. If the linguistic discourse approach is combined with the historical criticism approach, it will have advantages that are very helpful for researchers in the field of philology. One of its advantages, the ability to see the correspondence and parallels of the language used in a text with the language used at the time the text was written.